Fungal Protein – What Is It and What Is the Health Evidence? A Systematic Review Focusing on Mycoprotein - Derbyshire, Emma J.; Delange, Joanne (Frontiers in Sustainable Food Systems, 2021)
Mycoprotein is a protein-rich fungal-derived sustainable food source that was first discovered in the early 1960s. Since then, a sizeable body of research has investigated the health benefits of mycelium protein. Given this, the present publication aims to systematically review the effects of mycoprotein on human health. A literature search of human studies was conducted using PubMed Central, Clinical Trials.gov, Google Scholar and a manual search. Sixteen controlled trials, totaling 432 participants were included – of these 5 studies reported total cholesterol, 5 reported on energy intake, 7 on insulin levels, 8 on glucose levels and 4 studied protein response. Risk of bias showed that 7 studies were good quality although heterogeneity was apparent between studies. Results showed that acute mycoprotein ingestion was associated with reduced total cholesterol levels, particularly amongst those with hyperlipidemia and short-term energy intake. Evidence was less conclusive for effects on blood glucose and insulin levels. Mycoprotein also appears to be a promising bioavailable source of essential amino acids that induce muscle protein synthesis. Overall, given growing interest in sustainable proteins and accruing health evidence for mycoprotein, firmer embedment with food-based dietary guidelines is now worthy of consideration.